IMPLEMENTASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATERI IMAN KEPADA MALAIKATKELAS IV SDN 04 BARINGIN KOTA PADANG - Suwito (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Institut Agama Islam YAPTIP Chadijah Ismail Pasaman Barat, 2022)
This research is motivated by the low learning outcomes of PAI material on faith inAngels, class IV SDN 04 Baringin, Koto Tangah District, Padang City. The purpose ofthis study was to determine the increase in learning outcomes of faith in angels throughthe Problem Based Learning model. This type of research uses Classroom ActionResearch (CAR) with steps of planning (planning), implementation (acting), observation(observing) and reflection (reflecting). This CAR is carried out in three cycles. Cycle Iwas held on June 9, 2022 and Cycle II was held on June 22, 2022 and Cycle III was heldon June 30, 2022. The study was conducted in class IV SDN 04 Baringin Padang Citywith a total of 25 students consisting of 14 boys and 11 students. woman.The results showed that the Problem Based Learning (PBL) model could improvePAI learning outcomes on faith material to fourth grade angels at SDN 04 Baringin,Padang City. The increase in PAI learning outcomes on the material of faith in angels isknown by the test results in Cycle I, Cycle II and Cycle III which show an increase in theaverage value and the percentage of classical completeness. The average value ofstudents on the subject of faith in angels in the initial conditions (pre-cycle) was 74 withclassical completeness of 29% (8 students) from 25 students who achieved a score of 70(KKM score). Cycle I was 80 with classical completeness of 68% (17 students) whoachieved a score of 70 (KKM score). Cycle II was 82 with classical completeness 80%(20 students) who achieved a score of 70 (KKM score). And Cycle III was 86 with 96%classical completeness (24 students) who achieved a score of 70 (KKM score)